Biodegradable resin composition and film comprising same
By adding a specific content of carboxylic acid group-containing macromolecule and small molecule compounds to the polylactic acid biodegradable resin, the hydrolysis rate of polylactic acid is improved, and the problem of slow degradation of polylactic acid at room temperature composting conditions is solved, and a biodegradable resin composition with rapid degradation and stable performance is achieved.
Patent Information
- Application Number
- CN202410108013.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-07
- Filing Date
- 2024-01-25
- Publication Date
- 2025-03-07
AI Technical Summary
The existing polylactic acid biodegradable resins have slow degradation and degradation rates under normal temperature composting conditions, especially in environments with small bacterial content and low ambient temperatures, which are difficult to degrade quickly.
The biodegradable resin composition containing 50% by weight of polylactic acid resin, 0.5 to 5% by weight of a carboxylic acid group-containing macromolecular compound with a weight average molecular weight of 4000 to 30,000, and 0 to 2.5% by weight of a carboxylic acid group-containing small molecule compound with a weight average molecular weight of less than 4,000 is used to increase the content of carboxylic acid group and control the molecular weight, and promote the hydrolysis rate of polylactic acid.
The degradation rate of the biodegradable resin composition under soil burial or household compost conditions is significantly improved, allowing it to degrade rapidly, solving the problem of slow degradation of polylactic acid, while maintaining the performance stability of the product during its service life.
Smart Images

Figure BDA0004682922690000031 
Figure BDA0004682922690000151 
Figure BDA0004682922690000161
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer materials and relates to a biodegradable resin composition and a biodegradable resin composition film, a multilayer film, a packaging material film and an adhesive tape prepared therefrom. Background Art
[0002] Plastic is an important material used in all aspects of human production and life. However, most plastics can remain in nature for a long time after their service life ends. If they are not treated, they will cause pollution.
[0003] Biodegradable plastics can be decomposed by bacteria, and the use of such materials can effectively improve the above problems. At present, the more common biodegradable plastics on the market include: polylactic acid, polybutylene terephthalate adipate, polyhydroxyalkanoate, polybutylene succinate, polyglycolic acid, polycaprolactone, polypropylene carbonate, etc. Due to the excellent comprehensive performance of the processing performance and mechanical properties of polylactic acid, it is one of the most widely used biodegradable plastics. However, like other various resins, polylactic acid also has certain disadvantages when facing various uses. For example, the biodegradation rate of polylactic acid is slow, especially in an environment with less bacterial content and lower ambient temperature. That is, although polylactic acid can be identified as compostable by the standard method of industrial composting, it is often difficult to be identified by the standard method of soil burial or home composting, which means that it will not degrade quickly after being buried in the soil or home composting.
[0004] According to the literature Polym Eng Sci. 2020; 60: 2061-2075, under composting conditions, polylactic acid is degraded in two stages: (hydrolysis stage) polylactic acid first breaks the chain under the action of microbial secretions to form polylactic acid oligomers, lactic acid dimers and monomers, (microbial degradation stage) polylactic acid oligomers, lactic acid dimers and monomers are absorbed and metabolized by microorganisms. Under soil burial or household composting conditions, the hydrolysis stage is long, so increasing the hydrolysis rate is the key to increasing the degradation rate of polylactic acid.
[0005] In the past 20 years, most patents related to polylactic acid have focused on the manufacturing method of polylactic acid and the improvement of the mechanical properties of polylactic acid. There are few reports on increasing the degradation rate of polylactic acid during room-temperature composting. Patent WO 2021 / 185339A1 reports on the technical means of using small molecule organic acids to increase the hydrolysis rate of polylactic acid. However, during the composting process, some small molecule organic acids will seep out of the matrix material or be directly decomposed by microorganisms, resulting in the effect of increasing the hydrolysis rate being weakened. It can be seen that improving the degradability of polylactic acid under room-temperature composting conditions is still an unresolved problem.
[0006] Therefore, there is a need for a biodegradable resin composition with a higher hydrolysis rate, which can be rapidly degraded after being buried in soil or composted at home. Summary of the invention
[0007] In view of the above problems, the object of the present invention is to provide a biodegradable resin composition with a higher hydrolysis rate, which will degrade rapidly after being buried in soil or composted at home. Furthermore, the present invention also provides a film prepared using the biodegradable resin composition, a multilayer film, a packaging material and an adhesive tape processed using the film as a base material.
[0008] In order to solve the above problems, the present invention provides a biodegradable resin composition, which contains more than 50% by weight of polylactic acid resin, 0.5-5% by weight of a macromolecular compound containing a carboxylic acid group with a weight average molecular weight of 4000-30000, and 0-2.5% by weight of a small molecule compound containing a carboxylic acid group with a weight average molecular weight of less than 4000.
[0009] The polylactic acid is one or more homopolymers or copolymers of lactic acid. For homopolymers of lactic acid, it is preferred that the copolymerization unit contains 80-100 mol% of L-lactic acid or D-lactic acid and 0-20 mol% of their respective enantiomers. For copolymers of lactic acid, the copolymerization unit preferably contains 85-99 mol% of L-lactic acid or D-lactic acid. Polylactic acid can be obtained by dehydration polycondensation using lactic acid and other substances as raw materials; it can also be obtained by ring-opening polymerization from substances such as lactide. Among them, as lactide, cyclic dimer of L-lactic acid, i.e. L-lactide, cyclic dimer of D-lactic acid, i.e. D-lactide, meso-lactide obtained by cyclic dimerization of D-lactic acid and L-lactic acid, or racemic mixture of D-lactide and L-lactide, i.e. DL-lactide, can be cited. Any of the above lactides can be used in the present invention.
[0010] By making the content of the polylactic acid resin in the biodegradable resin composition be 50% by weight or more, the fracture strength of the film prepared by the composition of the present invention can be improved. Preferably, the content of the polylactic acid resin is 70% by weight or more, at which time the mechanical properties of the film prepared by the composition of the present invention are the best.
[0011] In addition, in order to promote the hydrolysis of the polylactic acid in the biodegradable resin composition, it is necessary to increase the carboxylic acid content in the biodegradable resin. By containing more than 0.5% by weight of the macromolecular compound containing the carboxylic acid group, it is possible to provide enough carboxylic acid groups for the biodegradable resin composition to promote the hydrolysis of the polylactic acid in the composition. By containing less than 5% by weight of the macromolecular compound containing the carboxylic acid group, the hydrolysis rate of the composition can be controlled within a reasonable limit, so that the product of the composition can not be affected by excessive hydrolysis and affect the performance within the service life. Furthermore, from the viewpoint of improving hydrolysis and ensuring usability, it is more preferred to contain 1-3% by weight of the macromolecular compound containing the carboxylic acid group.
[0012] Further, in order to ensure that the melt viscosity of the hot carboxylic acid-containing macromolecular compound itself is large enough, the molecular weight of the carboxylic acid-containing macromolecular compound cannot be too low, and in order to ensure that the carboxylic acid-containing macromolecular compound has sufficient acid value to promote the hydrolysis of polylactic acid, the weight average molecular weight of the carboxylic acid-containing macromolecular compound cannot be too high, and the weight average molecular weight of the carboxylic acid-containing macromolecular compound is 4000-30000. Preferably, the weight average molecular weight of the carboxylic acid-containing macromolecular compound is 6000-10000.
[0013] In order to ensure that the biodegradable resin composition has good thermal processability, the above carboxylic acid-containing macromolecular compound with a weight average molecular weight of 4000 to 30000 is a thermoplastic acrylic resin, and the thermoplastic acrylic resin has a structure shown in the following formula (1).
[0014]
[0015] Wherein, Q, R, and T represent other copolymer units, x, y, and m are integers greater than 1, and z and w are integers greater than 0.
[0016] The thermoplastic acrylic resin has two effects: (1) the carboxylic acid group in the thermoplastic acrylic resin can generate H+ and promote the hydrolysis of polylactic acid. (2) the thermoplastic acrylic resin is non-biodegradable and can persist in the biodegradable resin composition to exert the effect of (1).
[0017] Examples of other copolymerized units represented by Q, R, and T include styrene, methylstyrene, ethylstyrene, methacrylic acid, methyl methacrylate, methyl acrylate, ethyl acrylate, and butyl acrylate.
[0018] In order to improve the processability and increase the melt viscosity of the thermoplastic acrylic resin, in the formula (1), the other copolymer units represented by Q, R, and T are preferably styrene, methylstyrene, methacrylic acid, methyl methacrylate, and butyl acrylate. More preferably, in the formula (1), w=0, Q and R are each a styrene unit or a methylstyrene unit. In this case, the processability and melt viscosity of the thermoplastic acrylic resin are optimal.
[0019] Furthermore, in order to ensure that the biodegradable resin composition has sufficient hydrolysis performance, the acid value of the thermoplastic acrylic resin is 100-400 mg KOH / g. The acid value indicates the number of milligrams of potassium hydroxide (KOH) required to neutralize 1 gram of a chemical substance. The acid value is a measurement standard for the number of carboxylic acid groups of a substance. The higher the acid value, the higher the carboxylic acid group content of the thermoplastic acrylic resin. If the acid value is too low, the carboxylic acid group content of the thermoplastic acrylic resin is insufficient, and the hydrolysis-promoting effect on the biodegradable resin composition is not obvious; if the acid value is too high, the carboxylic acid group content of the thermoplastic acrylic resin is too high, and the biodegradable resin composition hydrolyzes too quickly, making it difficult to meet the use requirements. Further preferably, the acid value of the thermoplastic acrylic resin is 200-300 mg KOH / g.
[0020] Furthermore, in order to match the softening temperature of the thermoplastic acrylic resin and the softening temperature of the polylactic acid in the blending process of the biodegradable resin composition, the softening temperature of the thermoplastic acrylic resin is 120-180°C. When the softening temperature of the thermoplastic acrylic resin and the softening temperature of the polylactic acid in the blending process do not match, problems such as uneven feeding, insufficient mixing, and even blockage of the feeding port are likely to occur. Preferably, the softening temperature of the thermoplastic acrylic resin is 150-180°C.
[0021] Furthermore, in order to increase the hydrolysis rate of the biodegradable resin composition, the biodegradable resin composition of the present invention further comprises a small molecule compound containing a carboxylic acid group, wherein the weight average molecular weight of the small molecule compound containing a carboxylic acid group is less than 4000, and the content of the small molecule compound containing a carboxylic acid group is 0 to 2.5% by weight relative to the total amount of the biodegradable resin composition. Preferably, the content of the small molecule compound containing a carboxylic acid group is 0 to 1.5% by weight relative to the total amount of the biodegradable resin composition.
[0022] Furthermore, the carboxylic acid group-containing small molecule compound that promotes the hydrolysis of polylactic acid in the biodegradable resin composition cannot evaporate during the blending process, so the carboxylic acid group-containing small molecule compound with a weight average molecular weight of less than 4000 is at least one of a carboxylic acid with a carbon number of 3 or more and a hydroxycarboxylic acid compound.
[0023] Furthermore, in order to increase the hydrolysis rate of the biodegradable resin composition, the reactivity of the small molecule compound containing carboxylic acid groups cannot be too low, so the molecular weight of the small molecule compound containing carboxylic acid groups cannot be too high. At the same time, in order to ensure that it will not evaporate during the resin thermal processing, the molecular weight of the small molecule compound containing carboxylic acid groups cannot be too low. Therefore, the molecular weight of the small molecule compound containing carboxylic acid groups is between 50-1000.
[0024] Examples of the carboxylic acid group-containing compound include lactic acid, succinic acid, glutaric acid, 2-methyl-2-hydroxysuccinic acid, propylsuccinic acid, glutaric acid, 2-methyl-glutaric acid, 3-methyl-glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, dodecanedioic acid, galactaric acid, citric acid, cyclohexanecarboxylic acid, benzoic acid, naphthoic acid, tetrahydroxysuccinic acid, tetramethylsuccinic acid, aminovaleric acid, caproic acid, heptanoic acid, isoheptanoic acid, octanoic acid, aminooctanoic acid, isooctanoic acid, nonanoic acid, aminononanoic acid, decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid, heptadecanoic acid, octadecanoic acid, nonadecanoic acid, eicosanoic acid, docosanoic acid, tetracosanoic acid, hexacosanoic acid, triacontanoic acid, erucic acid, linoleic acid, linolenic acid, cinnamic acid, isodecanoic acid, Cinnamic acid, elaeolic acid, elaeolic acid, ricinoleic acid, 2-methylbutyric acid, 2-ethylbutyric acid, 4-methylnonanoic acid, 4-methyloctanoic acid, 2-hydroxysuccinic acid, tartaric acid, 3-methylpentanoic acid, 4-methylpentanoic acid, 3-methyl-2-oxopentanoic acid, 4-methyl-2-oxopentanoic acid, dihydroxymethylbutyric acid, 5-oxodecanoic acid, 5-oxododecanoic acid, 5-oxooctanoic acid, 2-oxoglutaric acid, 2-oxo-3-phenylpropionic acid, 3-hydroxybenzoic acid, cyclohexanecarboxylic acid, citric acid, bile acid, deoxycholic acid, phenoxyacetic acid, salicylic acid, tannic acid, 3-phenyl-2-acrylic acid, 2,6-pyridinedicarboxylic acid, 4-methoxybenzoic acid, methylenesuccinic acid, hexadienoic acid, propylene-1,2,3-tricarboxylic acid, folic acid, phenylacetic acid, 3-phenylpropionic acid, isophthalic acid, etc. From the perspective of simplifying processing difficulty, reducing dosage, reducing odor and easy acquisition, dibasic fatty acids such as adipic acid, suberic acid and sebacic acid are preferred.
[0025] Further, in order to increase the biodegradation rate and improve the properties of the biodegradable resin composition when it is made into products such as films, such as flexibility, elongation, thickness deviation, etc., the biodegradable resin composition also contains less than 30% by weight of a biodegradable resin other than polylactic acid, and the biodegradable resin other than polylactic acid can be selected from the group consisting of polyglycolic acid, polybutylene terephthalate adipate, polybutylene adipate succinate, polybutylene succinate, polycaprolactone, poly-3-hydroxybutyrate, copolymer of 3-hydroxybutyric acid and 3-hydroxyvaleric acid, copolymer of 3-hydroxybutyric acid and 3-hydroxycaproic acid, copolymer of 3-hydroxybutyric acid and 4-hydroxybutyric acid, polypropylene carbonate, and copolymers of at least one of the above polymer structure monomers and lactic acid. Preferably, the biodegradable resin other than polylactic acid is polycaprolactone.
[0026] Furthermore, the biodegradable resin composition has an intrinsic viscosity of more than 1.0 dL / g. The intrinsic viscosity (IV) is measured at 30°C using an Ubbelohde viscometer by dissolving the sample in chloroform, removing insoluble matter, and then preparing a solution of 3±1 mg / mL. The intrinsic viscosity can be used to characterize the molecular weight of the biodegradable resin composition. If the intrinsic viscosity is lower than 1.0 dL / g, the molecular weight of the resin is low, which may result in insufficient processing performance, mechanical properties, thermal properties and other performance characteristics. Therefore, the biodegradable resin composition of the present invention has an intrinsic viscosity of more than 1.0 dL / g. Preferably, the biodegradable resin composition of the present invention has an intrinsic viscosity of more than 1.2 dL / g.
[0027] Furthermore, the intrinsic viscosity loss rate of the biodegradable resin composition after treatment at 70°C, 85% RH, and 6 hours is greater than 15%. Such a biodegradable resin composition has a faster biodegradation rate. Preferably, the intrinsic viscosity loss rate is greater than 25%.
[0028] Further, due to production, processing and use requirements, the biodegradable resin composition has good exudation resistance, and the biodegradable resin composition is soaked in ethanol for 10 hours, and the intrinsic viscosity loss rate after treatment at 70°C, 85% RH, and 6 hours is more than 15%. Preferably, the biodegradable resin composition is soaked in ethanol for 10 hours, and the intrinsic viscosity loss rate after treatment at 70°C, 85% RH, and 6 hours is more than 25%.
[0029] Furthermore, in order to prevent the intrinsic viscosity loss rate of the biodegradable resin composition from decreasing due to the leakage of internal substances or contamination of other substances in contact with the composition during processing and application, the ethanol leakage rate of the biodegradable resin composition is less than 2%. More preferably, the ethanol leakage rate of the biodegradable resin composition is less than 1%.
[0030] The biodegradable resin described in the present invention may contain one or more additives such as fillers, plasticizers, extenders, end-capping agents, flame retardants, nucleating agents, antioxidants, lubricants, antistatic agents, antifogging agents, light stabilizers, ultraviolet absorbers, pigments, mildew-proof agents, antibacterial agents, or foaming agents, within the scope that does not hinder the achievement of the purpose of the present invention.
[0031] As the filler, fibrous, flaky, granular, or powdered fillers commonly used in the rubber and plastics industry can be used, including inorganic or organic fillers. As the inorganic filler, specifically one or more of fibrous inorganic fillers such as glass fiber, asbestos fiber, carbon fiber, graphite fiber, metal fiber, potassium titanate whisker, aluminum borate whisker, magnesium whisker, silicon whisker, wollastonite, sepiolite, asbestos, slag fiber, xonotlite, silica apatite, gypsum fiber, silica fiber, silica / alumina fiber, zirconium oxide fiber, boron nitride fiber, silicon nitride fiber or boron fiber can be cited, or One or more of the flaky or granular inorganic fillers such as glass flakes, non-swelling mica, swelling mica, graphite, metal foil, ceramic beads, talc, clay, mica, sericite, zeolite, bentonite, vermiculite, montmorillonite, dolomite, kaolin, micro-powdered silicic acid, feldspar powder, potassium titanate, fine hollow glass balls, calcium carbonate, magnesium carbonate, calcium sulfate, titanium dioxide, boehmite alumina, silicon oxide, gypsum, uniform quartzite, dawsonite or clay. As the organic filler, specifically, one or more of the plant fibers such as starch, cellulose, sisal fiber, or bamboo fiber, animal fibers such as wool fiber, and organic synthetic fibers such as aramid fiber or aromatic polyester fiber can be cited. The above fillers can be subjected to any form of surface treatment to enhance their interface adhesion with the resin.
[0032] The plasticizer is not particularly limited, and examples thereof include hydroxybenzoic acid-2-ethylhexyl ester and other hydroxybenzoic acid esters, polyol esters such as acetates of ethylene oxide adducts of glycerol, phthalic acid esters such as di-2-ethylhexyl phthalate, adipic acid esters such as dioctyl adipate, maleic acid esters such as di-n-butyl maleate, citrate esters such as acetylcitrate tributyl, or alkyl phosphates such as tricresyl phosphate, tricarboxylic acid esters such as trioctyl trimellitate, esters of succinic acid and triethylene glycol monomethyl ether, esters of adipic acid and diethylene glycol monomethyl ether, The present invention also includes alkyl ether esters of polycarboxylic acids such as esters formed by ether, or esters formed by 1,3,6-hexanic acid and polyethylene glycol monomethyl ether, acetylated polyoxyethylene alkyl (alkyl carbon number is 2-15) ethers such as acetylated polyoxyethylene hexyl ether, polyethylene glycol diacetate having an addition mole number of ethylene oxide of 3-20, polyoxyethylene-1,4-butylene glycol ether diacetate, polyethers of polyethylene glycol, polypropylene glycol, or polyethylene glycol-polypropylene glycol copolymers, oils and fats such as soybean oil or olive oil, or copolymers of the above chemical structures with polylactic acid, etc. Preferably, one or more of dioctyl phthalate, dibutyl phthalate, butyl benzyl phthalate, dioctyl sebacate, dibutyl sebacate, tributyl citrate, triethyl citrate, triethyl acetyl citrate, tributyl acetyl citrate, glyceryl triacetate, polyethylene glycol, polypropylene glycol, polyethylene glycol-polypropylene glycol copolymer, polylactic acid-ethylene glycol copolymer, polylactic acid-propylene glycol copolymer, soybean oil, or epoxidized soybean oil. The above-mentioned plasticizer can be used alone or in combination of two or more.
[0033] As the compatibilizer, compounds containing one or more of epoxy functional groups, isocyanate functional groups, carbodiimide functional groups, anhydride functional groups, silane functional groups, oxazoline functional groups, or phosphite functional groups can be listed, and the total number of the functional groups contained in the compound is more than two. Specifically, the compatibilizer can be one or more of toluene diisocyanate, diphenylmethane diisocyanate, p-xylylene diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate, lysine triisocyanate, γ-glycidyl ether oxygen propyl trimethoxy silane, polycarbodiimide, ethylene-acrylate-maleic anhydride terpolymer, or acrylic polymers with epoxy functional groups.
[0034] Examples of the end-capping agent include compounds containing one of epoxy functional groups, isocyanate functional groups, carbodiimide functional groups, acid anhydride functional groups, silane functional groups, oxazoline functional groups, and phosphite functional groups, and the total number of the functional groups contained in the compound is one.
[0035] The present invention also provides a biodegradable resin composition film prepared from the biodegradable resin composition.
[0036] The present invention also provides a multilayer film prepared from the above-mentioned biodegradable resin composition film. The multilayer film is a film having more than two layers. Since different layers can have different functions, compared with a single-layer film, a multilayer film can meet a variety of needs. For example, a biodegradable wallpaper having the above-mentioned biodegradable resin composition film with a printed pattern as the first layer, a glue layer as the second layer, and a release paper as the third layer. For example, a biodegradable capacitor film or electrode having the above-mentioned biodegradable resin film as the first layer and a metal layer as the second layer. Another example is a disposable raincoat material having the above-mentioned biodegradable resin composition film as the supporting layer and a waterproof coating layer as the waterproof layer.
[0037] The present invention also provides a packaging material film or adhesive tape prepared from the biodegradable resin composition. DETAILED DESCRIPTION
[0038] The present invention can be further understood through the specific examples and comparative examples of the present invention given below, but the scope of the present invention is not therefore limited to the following examples.
[0039] The materials used in the embodiments and comparative examples are as follows:
[0040] A1: Polylactic acid, manufactured by Total Corbion, specification: LX575, number average molecular weight: 100,000, biomass material, optical purity: 98%.
[0041] A2: Polylactic acid, manufactured by Total Corbion, specification: LX975, number average molecular weight: 100,000, biomass material, optical purity: 88%.
[0042] B1: acrylic resin, manufactured by Hanwha Corporation, Soluryl 160, acid value: 235 mgKOH / g, weight average molecular weight: 16500, acrylic acid-methacrylate-acrylate-styrene copolymer, softening temperature: 100°C.
[0043] B2: acrylic resin, manufactured by Hanwha Corporation, Soluryl S-820, acid value 205 mgKOH / g, weight average molecular weight 7300, styrene-methylstyrene-acrylic acid copolymer, softening temperature 158°C.
[0044] B3: acrylic resin, manufactured by Hanwha Corporation, Soluryl 840, acid value 238 mgKOH / g, weight average molecular weight 7200, methyl methacrylate-butyl acrylate-acrylic acid copolymer, softening temperature 120°C.
[0045] B4: acrylic resin, manufactured by Hanwha, Soluryl 60L, acid value 85 mgKOH / g, weight average molecular weight 6500, styrene-acrylic acid-acrylate copolymer, softening temperature 60°C.
[0046] B5: acrylic resin, manufactured by Hanwha Corporation, Soluryl 20, acid value: 232 mgKOH / g, weight average molecular weight: 2100, styrene-methylstyrene-acrylic acid copolymer, softening temperature: 120°C.
[0047] B6: acrylic resin, manufactured by Pioneer, BM72, acid value 6.5 mgKOH / g, weight average molecular weight 32,000, copolymer of methyl methacrylate and n-butyl methacrylate.
[0048] C1: citric acid, manufactured by Sinopharm, acid value 750 mgKOH / g, molecular weight 192, white powder.
[0049] C2: Sebacic acid, manufactured by Sinopharm, acid value 475 mgKOH / g, molecular weight 202, white powder.
[0050] C3: Adipic acid, manufactured by Sinopharm, acid value 650 mgKOH / g, molecular weight 146, white powder.
[0051] D1: polycaprolactone (PCL), manufactured by Hunan Juren Chemical New Materials Co., Ltd., specification: 6500, number average molecular weight 50,000.
[0052] D2: polybutylene succinate (PBS), manufactured by Blue Mountain Tunhe, specification: TH803S5, number average molecular weight 50,000.
[0053] The raw materials and samples used in the examples and comparative examples were tested according to the following experimental methods. Unless otherwise specified, the test conditions were all 23°C.
[0054] Intrinsic viscosity (IV): The sample is dissolved in chloroform, filtered through a sand core funnel with a pore size of 2 to 5 μm to remove insoluble matter, and then a chloroform solution with a solute content of 3±1 mg / mL is prepared. The effluent time T of the sample solution is measured at 30°C using an Ubbelohde viscometer with a capillary diameter of 0.3 to 0.4 mm. The effluent time To of pure chloroform is also tested under the same conditions. The intrinsic viscosity is calculated as follows:
[0055] IV=[ln(T / To)] / c
[0056] Intrinsic viscosity loss rate: The sample was placed in an Espec PL-2J constant temperature and humidity chamber for heat treatment. The heat treatment conditions were 70°C, 85% RH, and 6 hours. The intrinsic viscosity (IV1) of the sample before heat treatment and the intrinsic viscosity (IV2) of the sample after heat treatment were tested according to the above method. The intrinsic viscosity loss rate (ΔIV%) was calculated according to the following formula:
[0057] ΔIV%=(IV1-IV2) / IV1×100%
[0058] The loss rate of characteristic viscosity after 10 hours of ethanol immersion: Pour 500 ml of anhydrous ethanol into a transparent plastic box, cover the lid, preheat in a 40°C oven for 1 hour, soak the sample in the preheated anhydrous ethanol at 40°C for 10 hours, then wipe off the droplets on the surface with a dust-free cloth, vacuum dry at 23±2°C for 6 hours, and wipe the surface again with a dust-free cloth to remove dust. Then, place the sample in an Espec PL-2J constant temperature and humidity chamber for wet heat treatment. The wet heat treatment conditions are 70°C, 85% RH, and 6 hours. Test the characteristic viscosity (IV1) of the sample before wet heat treatment and the characteristic viscosity (IV2) of the sample after wet heat treatment according to the above method. Calculate the characteristic viscosity loss rate (ΔIV%) according to the following formula:
[0059] ΔIV%=(IV1-IV2) / IV1×100%
[0060] Acid value: Dissolve the sample of mass M g in methanol, add 2 drops of 0.1 wt% cresol red ethanol solution, calibrate with KOH standard solution of concentration N mg / mL, and take the solution from yellow to brown red and not fade within 15 seconds as the end point, record the volume of KOH standard solution used as V mL. Use the same volume of methanol, add 2 drops of 0.1 wt% cresol red ethanol solution, calibrate with KOH standard solution of concentration N mg / mL, and take the solution from yellow to brown red and not fade within 15 seconds as the end point, record the volume of KOH standard solution used as V0. Calculate the acid value according to the following formula:
[0061] Acid value = (V-V0) × N / M
[0062] Softening temperature: The biodegradable resin composition was molded at 200°C and quenched in ice water using a MINI TEST PRESS molding machine produced by TOYOSEIKI to prepare a molded product with a thickness of 1 mm. Three molded products were cut into squares with a side length of 10 mm or circles with a diameter of 10 mm, and stacked on the sample holder of a heat deformation Vicat testing machine produced by COESFELD. The softening temperature of the sample was tested under the conditions of a pressure of 10 N and a heating rate of 50°C / hr.
[0063] Weight average molecular weight: measured by Agilent 1260 gel permeation chromatograph (GPC) with tetrahydrofuran as mobile phase, measured 3 times and the average value was taken.
[0064] Thickness: The sample was cut into a 50 mm × 50 mm square, and the thickness at the four corners and the center was measured using a Mitutoyo low-force tabletop height gauge VL-50, and the average value of the five points was taken.
[0065] Ethanol exudation rate of the biodegradable resin composition: Pour 500 ml of anhydrous ethanol into a transparent plastic box, cover the lid, preheat in an oven at 40°C for 1 hour, weigh the initial weight of the sample m0, make the biodegradable resin composition into a sheet with a thickness of less than 100 μm, soak it in anhydrous ethanol preheated at 40°C for 10 hours, then wipe the droplets on the surface with a dust-free cloth, vacuum dry at 23±2°C for 6 hours, wipe the surface again with a dust-free cloth to remove dust, weigh the weight m, and calculate the ethanol exudation rate as follows:
[0066] Ethanol exudation rate = (m0-m) / m0×100%
[0067] Breaking strength and breaking elongation: The test piece with the size of 150 mm × 10 mm was made by DUMBBELL SD-100 test piece making machine. The tensile strength and breaking elongation of the test piece were measured by the tensile testing machine AG-IS1KN made by Shimadzu Corporation of Japan, with an intercept of 50 mm and a tensile speed of 100 mm / min. The test was repeated 5 times.
[0068] Examples 1 to 13 and Comparative Examples 1 to 7
[0069] The raw materials were kneaded at 190° C. and 100 rpm for 6 minutes using a C4150-01 internal mixer produced by TOYOSEIKI to prepare a biodegradable resin composition containing the components shown in Table 1.
[0070] Then, the biodegradable resin composition was molded at 200°C and quenched in ice water using a MINI TEST PRESS molding machine produced by TOYOSEIKI to prepare a molded product with a thickness of 200 μm. Then, a KARO-IV biaxial stretching machine produced by Bruckner was used to simultaneously stretch the biodegradable resin composition at 65°C and 5% / s at a stretching rate of 2.5×2.5 times and then heat-treat it at 132°C for 20 seconds, or to simultaneously stretch the biodegradable resin composition at 75°C and 5% / s at a stretching rate of 2.5×2.5 times and then heat-treat it at 138°C for 20 seconds to obtain a biodegradable resin composition film.
[0071] The performance of the films of the biodegradable resin compositions in the embodiments and comparative examples were tested by the above-mentioned testing methods. The test results of the resin compositions are listed in Tables 2 and 3.
[0072] The biodegradable resin composition of Example 3 uses a preferred embodiment, and the following examples and comparative examples are all described with Example 3 as a comparative example.
[0073] Example 1 is based on Example 3, and the type of small molecule compound containing a carboxylic acid group is changed to citric acid. Citric acid is easy to seep out of the biodegradable resin composition, so the ethanol seepage rate is relatively high. After being soaked in ethanol for 10 hours, the intrinsic viscosity loss rate is relatively low after treatment at 70°C, 85% RH, and 6 hours.
[0074] Example 1 is based on Example 3, and the type of small molecule compound containing a carboxylic acid group is changed to sebacic acid. The acid value of sebacic acid is lower than that of adipic acid. Therefore, after treatment at 70°C, 85% RH, and 6 hours, the intrinsic viscosity loss rate is lower.
[0075] Example 4 changes the type of carboxylic acid-containing macromolecular compound on the basis of Example 3. The carboxylic acid-containing macromolecular compound has a lower softening temperature and is difficult to mix evenly with other resins during the blending process. It has a smaller hydrolysis-promoting effect. Therefore, after treatment at 70°C, 85% RH, and 6 hours, the characteristic viscosity loss rate is lower.
[0076] Example 5 changes the type of carboxylic acid-containing macromolecular compound on the basis of Example 3. The softening temperature of the carboxylic acid-containing macromolecular compound is low, and it is difficult to mix evenly with other resins during the blending process, and the hydrolysis-promoting effect is small. Therefore, after treatment at 70°C, 85% RH, and 6 hours, the characteristic viscosity loss rate is low.
[0077] Example 6 changes the type of carboxylic acid-containing macromolecular compound on the basis of Example 3. The softening temperature of the carboxylic acid-containing macromolecular compound is relatively low, and it is difficult to mix evenly with other resins during the blending process. In addition, the acid value of the carboxylic acid-containing macromolecular compound is relatively low, and the hydrolysis-promoting effect is relatively small. Therefore, after treatment at 70°C, 85% RH, and 6 hours, the characteristic viscosity loss rate is relatively low.
[0078] In Example 7, based on Example 3, the content of the small molecule compound containing a carboxylic acid group is reduced to 0, resulting in a decrease in the carboxyl content of the biodegradable resin composition. Therefore, after treatment at 70° C., 85% RH, and 6 hours, the intrinsic viscosity loss rate is relatively low.
[0079] In Example 8, based on Example 3, the content of the small molecule compound containing a carboxylic acid group is increased to 2.5%, resulting in an increase in the carboxyl content of the biodegradable resin composition and an enhanced acid hydrolysis effect during the blending process, so that the intrinsic viscosity is greatly reduced.
[0080] In Example 9, based on Example 3, the content of the macromolecular compound containing a carboxylic acid group is reduced to 0.5%, resulting in a decrease in the carboxyl content of the biodegradable resin composition. Therefore, after treatment at 70°C, 85% RH, and 6 hours, the intrinsic viscosity loss rate is relatively low.
[0081] Example 10 increases the content of the macromolecular compound containing carboxylic acid groups to 5% based on Example 3, resulting in an increase in the carboxyl content of the biodegradable resin composition and an enhanced acid hydrolysis effect during the blending process, thereby significantly reducing the intrinsic viscosity.
[0082] In Example 11, based on Example 3, polycaprolactone is replaced with polybutylene succinate. Like polycaprolactone, polybutylene succinate is a resin with good toughness. Therefore, the elongation at break of Example 11 is close to that of Example 3.
[0083] Example 12 is based on Example 3, but polycaprolactone is removed. Since polylactic acid itself has a low elongation at break, the elongation at break of Example 12 is lower than that of Example 3.
[0084] Example 13 increases the content of polylactic acid with an optical purity of 98% on the basis of Example 3, resulting in improved crystallinity of the polylactic acid. Therefore, the loss rate of the characteristic viscosity after treatment at 70°C, 85% RH, and 6 hours is lower than that of Example 3.
[0085] Comparative Example 1 changes the type of carboxylic acid-containing macromolecular compound on the basis of Example 3. The molecular weight of the thermoplastic polyacrylic acid resin of the carboxylic acid-containing macromolecular compound is too low, and it migrates out of the matrix resin after being dissolved in ethanol. As a result, after ethanol immersion, the characteristic viscosity loss rate after treatment at 70°C, 85% RH, and 6 hours is greatly reduced, and the requirement of 15% cannot be met.
[0086] In Comparative Example 2, the type of macromolecular compound containing a carboxylic acid group is changed on the basis of Example 3. The molecular weight of the thermoplastic polyacrylic acid resin of the macromolecular compound containing a carboxylic acid group is too high, and the acid value is too low, and the ability to promote hydrolysis is insufficient, resulting in a significant decrease in the loss rate of the characteristic viscosity after ethanol immersion at 70°C, 85% RH, and 6 hours, which cannot meet the requirement of 15%.
[0087] Comparative Example 3 removes the carboxylic acid-containing macromolecular compound on the basis of Example 3, resulting in a significant reduction in the carboxyl content in the biodegradable resin composition and a reduced hydrolysis promotion effect. Therefore, the intrinsic viscosity loss rate after treatment at 70°C, 85% RH, and 6 hours is significantly reduced and cannot meet the 15% requirement.
[0088] Comparative Example 4 increases the content of the carboxylic acid-containing macromolecular compound to 6% on the basis of Example 3, resulting in an excessively high carboxyl content in the biodegradable resin composition. The acid hydrolysis effect is enhanced during the blending process, so the intrinsic viscosity is greatly reduced and cannot meet the requirement of 1.0 dL / g.
[0089] Comparative Example 5 increases the content of the small molecule compound containing carboxylic acid group to 3% on the basis of Example 3, resulting in an excessively large carboxyl content of the biodegradable resin composition. The acid hydrolysis effect is enhanced during the blending process, so the intrinsic viscosity is greatly reduced and cannot meet the requirement of 1.0 dL / g.
[0090] Comparative Example 6 removes the carboxylic acid group-containing macromolecular compounds and carboxylic acid group-containing small molecular compounds on the basis of Example 3, resulting in a significant reduction in the carboxyl content in the biodegradable resin composition and a reduction in the hydrolysis promotion effect. Therefore, the characteristic viscosity loss rate after treatment at 70°C, 85% RH, and 6 hours is greatly reduced and cannot meet the 15% requirement.
[0091] Comparative Example 7 is based on Comparative Example 6, but polycaprolactone is removed. Since the elongation at break of polylactic acid itself is low, the elongation at break is greatly reduced.
[0092] Table 1 Biodegradable resin composition composition
[0093]
[0094] Table 2 Properties of biodegradable resin composition (1)
[0095]
[0096] Table 3 Properties of biodegradable resin composition (2)
[0097]
Claims
1. A biodegradable resin composition, characterized in that The invention contains more than 50 wt% of polylactic acid resin, 0.5-5 wt% of a macromolecular compound containing a carboxylic acid group with a weight average molecular weight of 4000-30000, and 0-2.5 wt% of a small molecular compound containing a carboxylic acid group with a weight average molecular weight of less than 4000.
2. The biodegradable resin composition according to claim 1, characterized in that: The carboxylic acid-containing macromolecular compound with a weight average molecular weight of 4,000 to 30,000 is a thermoplastic acrylic resin.
3. The biodegradable resin composition according to claim 2, characterized in that: The thermoplastic acrylic resin has a structure represented by the following formula (1): In the formula, Q, R, and T represent other copolymer units, x, y, and m are integers greater than 1, and z and w are integers greater than 0.
4. The biodegradable resin composition according to claim 3, characterized in that: In the above formula (1), w=0, and Q and R are each a styrene unit or a methylstyrene unit.
5. The biodegradable resin composition according to claim 2, characterized in that: The acid value of the thermoplastic acrylic resin is 100-400 mg KOH / g.
6. The biodegradable resin composition according to claim 2, characterized in that: The softening temperature of the thermoplastic acrylic resin is 120-180°C.
7. The biodegradable resin composition according to claim 1, characterized in that: The small molecule compound containing a carboxylic acid group and having a weight average molecular weight of less than 4000 is at least one of a carboxylic acid and a hydroxycarboxylic acid compound having more than 3 carbon atoms.
8. The biodegradable resin composition according to claim 1, characterized in that: The weight average molecular weight of the small molecule compound containing carboxylic acid group with a weight average molecular weight less than 4000 is 50-1000.
9. The biodegradable resin composition according to claim 1, characterized in that: The invention also contains less than 30% by weight of a biodegradable resin other than polylactic acid, wherein the biodegradable resin other than polylactic acid is one or more selected from the group consisting of polyglycolic acid, polybutylene terephthalate adipate, polybutylene adipate succinate, polybutylene succinate, polycaprolactone, poly-3-hydroxybutyrate, a copolymer of 3-hydroxybutyric acid and 3-hydroxyvaleric acid, a copolymer of 3-hydroxybutyric acid and 3-hydroxyhexanoic acid, a copolymer of 3-hydroxybutyric acid and 4-hydroxybutyric acid, polypropylene carbonate, and a copolymer of at least one of the above polymer structural monomers and lactic acid.
10. The biodegradable resin composition according to claim 1, characterized in that: It has an intrinsic viscosity of 1.0 dL / g or more.
11. The biodegradable resin composition according to claim 1, characterized in that: The intrinsic viscosity loss rate after treatment at 70°C, 85% RH, and 6 hours was 15% or more.
12. The biodegradable resin composition according to claim 1, characterized in that: After immersion in ethanol for 10 hours, the intrinsic viscosity loss rate after treatment at 70°C, 85% RH, and 6 hours was more than 15%.
13. The biodegradable resin composition according to claim 1, characterized in that: The ethanol exudation rate was less than 2%.
14. A biodegradable resin film, prepared from the biodegradable resin composition according to any one of claims 1 to 13.
15. A multi-layer film comprising the biodegradable resin film according to claim 14.
16. A packaging film or tape, which is made of the biodegradable resin film according to claim 14 or the multilayer film according to claim 15.
Citation Information
Patent Citations
Biodegradable resin and film prepared thereby
WO2021185339A1